Long‐term outcomes after transcatheter aortic valve replacement with minimal contrast in chronic kidney disease. Issue 2 (12th November 2020) - Rzucidlo, Justyna; Jaspan, Vita; Paone, Darien; Jilaihawi, Hasan; Xia, Yuhe; Kapitman, Anna; Nakashima, Makoto; He, Yuxin; Ibrahim, Homam; Pushkar, Illya; Neuburger, Peter J.; Saric, Muhamed; et al.
Abstract: Background: Patients with renal insufficiency have poor short‐term outcomes after transcatheter aortic valve replacement (TAVR). Methods: Retrospective chart review identified 575 consecutive patients not on hemodialysis who underwent TAVR between September 2014 and January 2017. Outcomes were defined by VARC‐2 criteria. Primary outcome of all‐cause mortality was evaluated at a median follow‐up of 811 days (interquartile range 125–1, 151). Results: Preprocedural glomerular filtration rate (GFR) was ≥60 ml/min in 51.7%, 30–60 ml/min in 42.1%, and < 30 ml/min in 6.3%. Use of transfemoral access (98.8%) and achieved device success (91.0%) did not differ among groups, but less contrast was used with lower GFR (23 ml [15–33], 24 ml [14–33], 13 ml [8–20]; p  < .001). Peri‐procedural stroke (0.7%, 2.1%, 11.1%; p  < .001) was higher with lower GFR. Core lab analysis of preprocedural computed tomography scans of patients who developed a peri‐procedural stroke identified potential anatomic substrate for stroke in three out of four patients with GFR 30–60 ml/min and all three with GFR <30 ml/min (severe atheroma was the most common subtype of anatomical substrate present). Compared to GFR ≥60 ml/min, all‐cause mortality was higher with GFR 30–60 ml/min (HR 1.61 [1.00–2.59]; aHR 1.61 [0.91–2.83]) and GFR <30 ml/min (HR 2.41 [1.06–5.48]; aHR 2.34 [0.90–6.09]) but not significant after multivariable adjustment. Follow‐up echocardiographic data, available in 63%, demonstrated no difference in structural heart valve deterioration over time among groups. Conclusions: Patients with baseline renal insufficiency remain a challenging population with poor long‐term outcomes despite procedural optimization with a transfemoral‐first and an extremely low‐contrast approach.